Dissociating Profiles of Social Cognitive Disturbances Between Mixed Personality and Anxiety Disorder - Czekóová, Kristína; Shaw, Daniel Joel; Pokorná, Zuzana; Brázdil, Milan (Frontiers in Psychology, 2020)
BACKGROUND: An emerging body of research has begun to elucidate disturbances to social cognition in specific personality disorders (PDs). No research has been conducted on patients with Mixed Personality Disorder (MPD), however, who meet multiple diagnostic criteria. Further, very few studies have compared social cognition between patients with PD and those presenting with symptomatic diagnoses that co-occur with personality pathologies, such as anxiety disorder (AD). The aim of this study was to provide a detailed characterization of deficits to various aspects of social cognition in MPD and dissociate impairments specific to MPD from those exhibited by patients with AD who differ in the severity of personality pathology. METHOD: Building on our previous research, we administered a large battery of self-report and performance-based measures of social cognition to age-, sex- and education-matched groups of patients with MPD or AD, and healthy control participants (HCs; n=29, 23 and 54, respectively). This permitted a detailed profiling of these clinical groups according to impairments in emotion recognition and regulation, imitative control, low-level visual perspective taking, and empathic awareness and expression. RESULTS: The MPD group demonstrated poorer emotion recognition for negative facial expressions relative to both HCs and AD. Compared with HCs, both clinical groups also performed significantly worse in visual perspective taking and interference resolution, and reported higher personal distress when empathizing and more state-oriented emotion regulation. CONCLUSION: We interpret our results to reflect dysfunctional cognitive control that is common to patients with both MPD and AD. Given the patterns of affective dispositions that characterize these two diagnostic groups, we suggest that prolonged negative affectivity is associated with inflexible styles of emotion regulation and attribution. This might potentiate the interpersonal dysfunction exhibited in MPD, particularly in negatively valenced and challenging social situations.